In-Situ Process and Simulation of High-Performance Piezoelectric-on-Silicon Substrate for SAW Sensor - Ma, Rui; Liu, Weiguo; Sun, Xueping; Zhou, Shun (Frontiers in Materials, 2021)
This paper studied the manufacturing process of Piezoelectric-on-Silicon (POS) substrate which integrates 128° Y-X Lithium niobate thin film and silicon wafer using Smart-cut technology. The blistering and exfoliation processes of He as-implanted LN crystal under different annealing temperatures are observed by in-situ method. Unlike the conventional polishing process, the stripping mechanism of the Lithium niobate thin film is changed by controlling annealing temperature, which can improve the surface morphology of the peeling lithium niobate thin film. We prepared the 128° Y-X POS substrate with high single-crystal Lithium niobate thin film and surface roughness of 3.91 nm by Benzocyclobutene bonding. After simulated the surface acoustic wave (SAW) characteristics of the POS substrate, the results demonstrate that the Benzocyclobutene layer not only performs as a bonding layer but also can couples more SAW vibration into the LN thin film. The electromechanical coupling coefficient of POS substrate is up to 7.59% in the Rayleigh mode when hLN /λ is 0.3 and hBCB /λ is 0.1. Therefore, as a high performance substrate material, the POS substrate has proved to be an efficient method to miniaturize and integrate the SAW sensor.